Case Report: Appearance of Various Disease-Specific Antibodies After the Onset of Dipeptidyl Peptidase-4 Inhibitor-Associated Bullous Pemphigoid - Iwamoto, Yuichiro; Anno, Takatoshi; Koyama, Katsumasa; Kawasaki, Fumiko; Kaku, Kohei; Tomoda, Koichi; Sugiyama, Seiko; Aoyama, Yumi; Kaneto, Hideaki (Frontiers in Immunology, 2022)
Bullous pemphigoid (BP) is a rare autoimmune blistering disease, and the prevalence of type 2 diabetes mellitus (T2DM) is relatively high in subjects with BP. It is known that dipeptidyl peptidase-4 inhibitor (DPP-4i), one kind of antidiabetic drugs, can cause BP, although precise mechanism of DPP-4i-related BP remains unclear. In this report, we showed a case with appearance of various disease-specific antibodies after the onset of DPP-4i-related BP. Furthermore, various disease-specific antibodies became positive and showed high titers two years after the onset of DPP-4i-related BP and discontinuation of DPP-4i. These data showed that it is possible for immune tolerance to be broken after the onset of DPP-4i-related BP, and it may be important to check autoimmune antibodies in DPP-4i-related BP subjects even when BP symptoms are improved.